Chronic hepatitis in childhood: the spectrum of the disease. Issue 5 (May 1988) - Bortolotti, F; Calzia, R; Vegnente, A; Cadrobbi, P; Rugge, M; Armigliato, M; Marazzi, M G; Iorio, R; Crivellaro, C; Piscopo, R
Abstract : During a multicentre study of chronic hepatitis in childhood diagnosed by biopsy, the spectrum of the disease has been evaluated in 196 consecutive patients, including 157 from Northern Italy and 39 from Southern Italy. Only 31% of patients in the former group and 27% in the latter were symptomatic when first seen: the majority of cases being seen after familial screenings for hepatitis B virus (HBV) markers or during intercurrent infections, thus suggesting that the frequency of chronic hepatitis in childhood might be largely underestimated in our area. In Southern and Northern Italy 83% of symptomatic and 95% of asymptomatic patients were hepatitis B surface antigen (HBsAg) positive in serum; only 15 (8.3%) of these children were born to mothers known to be HBsAg positive at delivery, but a high circulation of HBV was found in their families: in fact more than 65% of household contacts in Northern Italy and more than 90% in Southern Italy had serological evidence of past or ongoing HBV infection. These data indicate that, although familial screenings for HBV could have enhanced the percentage of HBsAg positive asymptomatic cases, chronic hepatitis in Italian children is mainly caused by HBV infection acquired in the familial setting through horizontal transmission. Such findings also emphasise the importance of mass vaccination of infants as the most effective means to prevent chronic type B hepatitis in childhood in our area. Among HBsAg positive children 55% had histological features of chronic active hepatitis and 85% were hepatitis Be antigen (HBeAg) positive in serum. Anti-HBe positive hepatitis was significantly more frequent in Southern than in Northern Italy in parallel with the significantly higher prevalence (17%) of hepatitis delta virus infection in that area. Of the 16 HBsAg negative cases included in the study three had autoimmune hepatitis, three Wilson's disease, one alpha1 antitrypsin deficiency, and nine had cryptogenic hepatitis, often associated to mild liver lesions resembling those seen in our adult patients with chronic non-A, non-B hepatitis unrelated to percutaneous exposure.